2009
DOI: 10.5194/acp-9-9433-2009
|View full text |Cite
|
Sign up to set email alerts
|

H<sub>2</sub><sup>16</sup>O and HDO measurements with IASI/MetOp

Abstract: Abstract.In this paper we analyze distributions of water vapour isotopologues in the troposphere using infrared spectra recorded by the Infrared Atmospheric Sounding Interferometer (IASI), which operates onboard the Metop satellite in nadir geometry. The simultaneous uncorrelated retrievals of H 16 2 O and HDO are performed on radiance measurements using a line-by-line radiative transfer model and an inversion procedure based on the Optimal Estimation Method (OEM). The characterizations of the retrieved produc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 47 publications
1
53
0
Order By: Relevance
“…Interferometer) is an atmospheric interferometer working in the infrared, launched in 2006 on the METOP-A satellite (Phulpin et al 2007;Pougatchev et al 2008;Herbin et al 2009;Clerbaux et al 2009). The data are available at the website of the Centre for Atmospheric Chemistry Products and Services 1 .…”
Section: Iasi (Infrared Atmospheric Soundingmentioning
confidence: 99%
“…Interferometer) is an atmospheric interferometer working in the infrared, launched in 2006 on the METOP-A satellite (Phulpin et al 2007;Pougatchev et al 2008;Herbin et al 2009;Clerbaux et al 2009). The data are available at the website of the Centre for Atmospheric Chemistry Products and Services 1 .…”
Section: Iasi (Infrared Atmospheric Soundingmentioning
confidence: 99%
“…Work performed from high spectral measurements in the thermal infrared (TIR), such as AIRS (Crevoisier et al, 2003;Engelen and Stephens, 2004;Divakarla et al, 2006;Chahine et al, 2008;Maddy et al, 2008;Xiong et al, 2008), TES (Shepard et al, 2008;Kulawik et al, 2010;Worden et al, 2012) and IASI (Crevoisier et al, 2009;Herbin et al, 2009;Razavi et al;, has demonstrated the sensitivity of these observations to the midtroposphere. Moreover, the OCO's pre-launch studies (Connor et al, 2008;Butz et al, 2009) as well as those from the shortwave infrared (SWIR) instrument SCIAMACHY Noël et al, 2005) have illustrated the ability of such measurements to get information on gaseous concentrations near the surface.…”
Section: Introductionmentioning
confidence: 99%
“…In the upper troposphere, the water vapor isotopic composition can be measured by satellites (Kuang et al, 2003;Nassar et al, 2007;Steinwagner et al, 2010) or in situ (Webster and Heymsfield, 2003;Sayres et al, 2010) and reflects the role of convection in the transport of water in the upper troposphere and through the tropopause (Moyer et al, 1996). In the mid-troposphere, the water vapor isotopic composition can also be measured by satellite (Worden et al, 2007;Herbin et al, 2009;Schneider and Hase, 2011) and in situ and may give an indication about water cycle processes such as mixing of air masses (Galewsky and Hurley, 2010) or rain reevaporation (Worden et al, 2007).…”
Section: Introductionmentioning
confidence: 99%